Analysis of parents’ factors in providing developmental stimulation among pre-school age children in Pakis Sub-District, Malang, East Java - Mansur, Herawati; Setyaningsih, Wahyu (Universitas Udayana, 2021)
Background and purpose: Lack of stimulation can cause deviations in child development and even permanent disturbances. The purpose of the study is to determine parenting factors in providing developmental stimulation in pre-school age children in Pakis Sub-District, Malang City, East Java.Methods: This was a cross-sectional study of 120 mothers who have pre-school age children in Curah Ampel Village, Pakis Sub-District, Malang, conducted from September-November 2018. Data were collected with self-administered questionnaire. The questionnaire consists of mothers’ demographic characteristics (age, education, and employment), father’s involvement, knowledge about development stimulation, parenting style, and parental stimulation. Data analysis were including univariable, bivariable, and multivariable analysis conducted with STATA. Results: On average, mother’s age was 30 years old, 70.0% with low education, and 83.3% were unemployed. This study found that 55% of parents provide stimulation development that falls in the poor categories. From the result of multivariable analysis with logistic regression, it was found that mother’s education associated with parental stimulation to pre-school age children (OR=0.322, 95%CI: 0.121-0.858, p=0.023). Conclusions: This study highlights that mother’s educational background has an important role in providing parental stimulation. Poor parental stimulation can cause developmental delays. A parenting program is needed to develop the knowledge and the ability of parents in accompanying every phase of their child development.